Biomechanical testing of a PEEK-based dynamic instrumentation device in a lumbar spine model. (May 2017) - Herren, Christian; Beckmann, Agnes; Meyer, Sabine; Pishnamaz, Miguel; Mundt, Marion; Sobottke, Rolf; Prescher, Andreas; Stoffel, Marcus; Markert, Bernd; Kobbe, Philipp; Pape, Hans-Christoph; Eysel, Peer; et al.
Abstract: Background: The purpose of this study was to investigate the range-of-motion after posterior polyetheretherketone-based rod stabilisation combined with a dynamic silicone hinge in order to compare it with titanium rigid stabilisation. Methods: Five human cadaveric lumbar spines with four vertebra each (L2 to L5) were tested in a temperature adjustable spine-testing set-up in four trials: (1) native measurement; (2) kinematics after rigid monosegmental titanium rod instrumentation with anterior intervertebral bracing of the segment L4/5; (3) kinematics after hybrid posterior polyetheretherketone rod instrumentation combined with a silicone hinge within the adjacent level (L3/4) and (4) kinematics after additional decompression with laminectomy of L4 and bilateral resection of the inferior articular processes (L3). During all steps, the specimens were loaded quasi-statically with 1°/s with pure moment up to 7.5 Nm in flexion/extension, lateral bending and axial rotation. Findings: In comparison to the native cadaveric spine, both the titanium device and polyetheretherketone-based device reduce the range-of-motion within the level L4/5 significantly (flexion/extension: reduction of 77%, p < 0.001; lateral bending: reduction of 62%, p < 0.001; axial rotation: reduction of 71%, p < 0.001). There was a clear stabilisation effect after hybrid-instrumentation within the level L3/4, especially in flexion/extension (64%, p < 0.001) and lateral bending (62%, p < 0.001) but without any effect on the axial rotation. Any temperature dependency has not been observed. Interpretation: Surprisingly, the hybrid device compensates for laminectomy L4 and destabilising procedure within the level L3/4 in comparison to other implants. Further studies must be performed to show its effectiveness regarding the adjacent segment instability. Highlights: The PEEK-based and the titanium rod reduce the range-of-motion after instrumentation. No signs of hypermobility have been observed in the superior adjacent level. The dynamic construct constrained motions in flexion/extension and lateral bending. Partial resection of the facet joint has no influence on stability. Any temperature dependency has not been observed.